Preparation method and application of self-supporting iron-nickel-boron loaded foamed nickel composite material

The self-supported iron-nickel-boron-supported foam nickel composite material is prepared by alternating impregnation methods, which solves the problems of complex preparation methods of existing bimetallic borides and difficulty in catalyst recovery, and achieves efficient and economical catalytic performance and environmentally friendly process flow.

CN119819306AActive Publication Date: 2025-04-15HEFEI UNIV OF TECH

Patent Information

Application Number
CN202510189660.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-15
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The existing preparation methods of bimetallic borides are complex and time-consuming, which affects the catalytic performance. The violent reactions during the reaction can easily lead to agglomeration, making it difficult to recover the catalyst, limiting its widespread and economical application.

Method used

The foam nickel foam is alternately immersed in the reducing agent solution and the iron precursor solution by alternating impregnation method, which promotes the metal ions to autocatalyze the growth of iron nickel borides on the surface of the foam nickel foam, and prepares a foam nickel composite material supported by supporting iron nickel boron.

Benefits of technology

It has achieved simple process, short preparation period, low energy consumption, high catalytic performance, easy recovery and recycling of catalysts, and solved the problems of sediment aggregation, uneven loading, low specific surface area and poor catalytic activity in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819306A_ABST
    Figure CN119819306A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a self-supporting iron-nickel-boron-loaded foamed nickel composite material, and the preparation method comprises the following steps: alternately immersing foamed nickel into a reducing agent solution and an iron precursor solution by adopting an alternate immersion method to promote metal ions to grow iron-nickel-boride on the surface of the foamed nickel in an autocatalytic manner, thereby obtaining the self-supporting iron-nickel-boron-loaded foamed nickel composite material. And thus, the self-supporting iron-nickel-boron loaded foam nickel composite material is obtained. The composite material can be used for assembling a catalyst module, activating periodate and realizing complete degradation of chlorophenol compounds. The prepared self-supporting composite material has high catalytic activity and stability, active components are uniformly and firmly distributed, a catalyst module constructed based on the self-supporting composite material effectively avoids separation and recovery difficulty of a powder catalyst in practical application, modular management and large-scale amplification are facilitated, and the self-supporting composite material has a wide application prospect and is suitable for industrial production. Especially in the technical field of environmental engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a self-supporting iron-nickel-boron loaded nickel foam composite material and application of the composite material in treating chlorophenol organic pollutants with heterogeneous activated periodate, belonging to the technical field of environmental engineering. Background Art

[0002] Chlorophenols (CPs) are a general term for chlorine-substituted phenol compounds, and their basic structure is that chlorine replaces the hydrogen atom on the benzene ring. Chlorophenols have strong endocrine disruption ability, genotoxicity, bioaccumulation ability, cytotoxicity and carcinogenicity. Some intermediates of chlorophenols are even more toxic. Due to the high chemical inertness of the C-Cl bond on the aromatic ring, traditional removal methods often have shortcomings in efficiency, selectivity and environmental sustainability. Therefore, it is crucial to develop effective removal technologies for chlorophenols. In this regard, advanced oxidation processes based on periodate (PI) are widely used in the removal of stubborn organic pollutants due to their simple operation and strong oxidation ability. However, due to the relatively low redox potential (+1.6 eV) of periodate, its ability to oxidize organic pollutants itself is limited. Generally, periodate can be activated by ultraviolet light, ultrasound, sunlight, microwaves, freezing, transition metal compounds, etc. to generate reactive substances or degrade pollutants through non-radical pathways. However, these methods have the disadvantages of high energy input, secondary pollution (such as metal leaching) and inherent defects in the free radical activation pathway (susceptibility to interference in water matrix environments), which limit their application in periodate activation processes. Therefore, the development of catalysts with higher activity and stability is the key to the widespread application of periodate.

[0003] Boron, as a metalloid element, is located between beryllium and carbon in the periodic table and has a superior ability to combine with a variety of metals or non-metallic elements. Currently, boron-based catalysts have shown great potential in advanced oxidation processes. In order to improve the catalytic performance of boron-based catalysts, researchers have developed a variety of methods, including composition regulation, active material hybridization and structural engineering. Compared with monometallic borides, bimetallic borides have stronger catalytic performance and have therefore attracted widespread attention. Multimetallic coordination improves electronic conductivity and promotes the formation of abundant active sites, which is helpful for catalytic applications. In particular, iron-nickel borides exhibit excellent catalytic activity because they are easy to synthesize in simple chemical processes and can work stably in a wide pH range. However, the existing preparation methods of bimetallic borides are usually complicated and time-consuming, which may have a negative impact on the catalytic performance. Moreover, the violent reaction during the reaction process easily leads to agglomeration, making it difficult to recover the catalyst, further limiting its wide application and economic feasibility.

[0004] In order to solve this problem, one strategy is to load the boride onto a regular carrier with a high specific surface area and rich pore structure. This not only achieves the effective fixation of the boride, but also makes full use of the structural advantages of the carrier. Nickel foam materials have become ideal materials for treating organic pollutants due to their excellent mechanical properties, uniform pore distribution, chemical stability, good corrosion resistance and excellent anti-clogging properties. Although the use of a carrier is a good strategy, the traditional preparation method usually requires additional binding materials and is complicated to operate, which is not only time-consuming, but also not conducive to improving catalytic performance. For example, patent CN109119257A proposes a method for directly depositing iron, cobalt and boron on nickel foam using a chemical reduction method. The method first pre-treats the nickel foam with hydrochloric acid, then immerses it in a transition metal salt solution, and quickly drips a reducing solution for reduction deposition. Although the chemical reduction method is simple, the resulting deposits often aggregate together, resulting in uneven loading, reduced specific surface area and catalytic activity, and the resulting cobalt iron boride material is physically coated on the surface of the nickel foam, not directly grown on the nickel foam, and it is difficult to prevent the deposit from falling off and the leaching of ions during the reaction. Patent CN117684201A discloses a method for preparing a porous nickel-molybdenum material with in-situ dual-phase boride loading. The method first prepares a porous nickel-molybdenum alloy substrate by etching, then reacts it with boron powder, and synthesizes Mo2NiB2 / Ni3B dual-phase boride on the substrate surface by solid phase boriding process. Although this method can achieve the loading of dual-phase boride, it has complex process, long synthesis time, high energy consumption, and may cause environmental pollution and high cost problems, which limits its feasibility of large-scale synthesis.

[0005] In summary, although there are many methods for developing efficient boron-based catalysts to improve their catalytic performance, these methods generally have the disadvantages of pollution problems, cumbersome operations, high raw material costs and high energy consumption, which limit their efficiency and economy in practical applications. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a self-supporting iron-nickel-boron loaded nickel foam composite material, and applies it to the treatment of chlorophenol organic pollutants in heterogeneous activated periodate. The present invention aims to solve the following technical problems: difficulty in separating and recovering powdered catalysts; poor catalytic effect of the overall catalyst, uneven distribution of active components, weak self-supporting ability, high energy consumption in the preparation process, large ion leaching, and how to simply and efficiently treat organic pollutants.

[0007] To achieve the above objectives, the present invention provides the following technical solutions:

[0008] A method for preparing a self-supporting iron-nickel-boron loaded nickel foam composite material, characterized in that: firstly, the oxide layer and impurities on the surface of the nickel foam are removed by pretreatment, and then the nickel foam is alternately immersed in a reducing agent solution and an iron precursor solution by an alternating immersion method, so as to promote the metal ions to self-catalytically grow iron-nickel boride on the surface of the nickel foam, and finally obtain a self-supporting iron-nickel-boron loaded nickel foam composite material. The specific steps are as follows:

[0009] Step 1: Cut the nickel foam into appropriate sizes, place it in a hydrochloric acid solution for treatment, then wash it with deionized water and anhydrous ethanol in turn, and finally place it in a drying oven to dry.

[0010] Step 2: dissolving iron salt in deionized water to prepare a 10-20wt% iron precursor solution; dissolving sodium borohydride in deionized water to prepare a 5-10wt% reducing agent solution, and using 0.1-1.0M sodium hydroxide to adjust the solution pH to greater than 10 to prevent self-decomposition of sodium borohydride.

[0011] Step 3: immerse the nickel foam in a reducing agent solution, and let it stand for 10-20 seconds after bubbles are observed; then quickly immerse it in an iron precursor solution, and take it out after fully reacting for 10-20 seconds.

[0012] Step 4: Repeat the immersion process of step 3 until the nickel foam is immersed in the reducing agent solution and no more bubbles are generated. The obtained product is washed and dried to obtain a self-supporting iron-nickel-boron loaded nickel foam composite material.

[0013] Preferably, in step 1, the concentration of the hydrochloric acid solution is 1M.

[0014] Preferably, in step 2, the iron salt may be selected from ferrous chloride tetrahydrate or ferrous sulfate heptahydrate.

[0015] Preferably, the drying conditions in step 1 and step 4 are drying at 60-80° C. for 8-12 hours.

[0016] The self-supporting iron-nickel-boron loaded nickel foam composite material prepared by the present invention can be used as a heterogeneous catalyst to activate periodate and be applied to the degradation of chlorophenol organic pollutants. The specific application method is as follows:

[0017] First, a chlorophenol organic pollutant treatment device is built; multiple self-supporting iron-nickel-boron loaded nickel foam composite materials are assembled into a catalyst module, and the catalyst module is installed as a reaction unit in the chlorophenol organic pollutant treatment device. The mixed waste liquid of chlorophenol organic pollutants and periodate will flow through the catalyst module. During this process, periodate is activated to produce highly active free radicals, thereby achieving complete degradation of chlorophenol organic pollutants.

[0018] Catalyst module characteristics: The catalyst module can be self-supporting without adhesives and has excellent self-supporting ability. This makes it possible to easily adjust the size of the catalyst module by flexibly increasing or decreasing the amount of Fe-Ni-B-loaded nickel foam composite material without destroying the catalyst module to meet the processing needs of different scales.

[0019] Preferably, the periodate comprises at least one of potassium periodate and sodium periodate.

[0020] Preferably, the chlorophenol organic pollutant includes at least one of 4-chlorophenol, 2,4-dichlorophenol and 2,4,6-trichlorophenol.

[0021] As preferably, the chlorophenol organic pollutant treatment device is composed of the following parts: an oxidant storage tank, an organic pollutant tank, a mixing kettle, and a degradation reaction tank, in which multiple groups of catalyst modules are arranged along the pollutant flow direction in the degradation reaction tank. During operation, the waste liquid containing chlorophenol organic pollutants and the periodate solution from the oxidant storage tank are sent to the mixing kettle by a centrifugal pump for uniform stirring, and then transported to the degradation reaction tank by a centrifugal pump. In the degradation reaction tank, multiple catalyst modules are arranged in the flow direction to become the place where the oxidation reaction of organic pollutants occurs. Through the catalytic action of the iron-nickel-boron loaded nickel foam composite material, periodate decomposes to produce active free radicals, and the electron transfer pathway mineralizes the organic pollutants in the solution into CO2 and H2O. After the chlorophenol organic pollutant treatment reaches the standard, the wastewater can be discharged safely.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] (1) The preparation method of the self-supporting iron-nickel-boron loaded nickel foam composite material provided by the present invention adopts an alternating impregnation autocatalytic growth strategy for one-step synthesis. The method has the advantages of simple process, short preparation cycle, mild reaction conditions, low energy consumption in the preparation process, small footprint of the reaction equipment, environmental friendliness, and potential for large-scale batch production.

[0024] (2) The method for preparing the self-supporting iron-nickel-boron loaded nickel foam composite material provided by the present invention can effectively generate uniformly dispersed layered iron-nickel boride by precisely controlling the growth process of iron-nickel-boron through alternating impregnation. The unique layered porous structure forms a large amount of void space, providing abundant contact areas and multiple transmission channels for reactants, thereby significantly improving the catalytic performance. The present invention successfully overcomes the problems of sediment aggregation, uneven loading, low specific surface area and poor catalytic activity in traditional methods.

[0025] (3) The self-supporting iron-nickel-boron loaded nickel foam composite material prepared by the present invention uses nickel foam as a matrix. The nickel foam directly reacts with the reducing solution to provide an anchor point for the growth of iron-nickel-boron. The iron-nickel-boron grows directly on the nickel foam, so that a seamless connection is formed between the nickel foam and the iron-nickel-boron, forming a fully connected overall structure with a firm combination, which effectively improves the electron transfer rate and can effectively avoid the problems of active component shedding and ion leaching during catalytic applications.

[0026] (4) The method of the present invention uses nickel foam itself as a nickel source, which simplifies the operation process, significantly reduces costs, and improves environmental friendliness. In addition, by adjusting the amount of synthetic liquid, the size and proportion of the catalyst can be customized according to demand, meeting the requirements of large-scale production of commercial catalysts.

[0027] (5) The self-supporting iron-nickel-boron loaded nickel foam composite material prepared by the present invention exhibits excellent catalytic efficiency and stability by virtue of the synergistic effect of metal boride and bimetallic composite material, and successfully solves the limitations of traditional Fenton-type reactions. Bimetallic boride stimulates the high catalytic activity of the material by regulating the electronic structure and surface reconstruction of the active site. Boron-mediated reverse electron transfer enhances the electron enrichment of the metal site, and the surface reconstruction forms active hydroxides, further improving the activity of the catalytic active site. In addition, the three-dimensional structure of nickel foam provides a large specific surface area, which can expose abundant active sites and promote the transfer of pollutants to the active sites. The experimental results show that the composite material of the present invention achieves 100% degradation efficiency of chlorophenol compounds during the periodate activation process, and can be directly applied without any post-treatment. The material is easy to operate, does not require additional energy input, and the catalyst is easy to recover and recycle, which simplifies the process flow, significantly reduces costs, and fully complies with the principle of green environmental protection. The design effectively solves the problem of separation and recovery of traditional powder catalysts, while supporting modular management and large-scale expansion of oxidation degradation tanks, showing excellent performance and broad application potential in the field of environmental engineering technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The scanning electron microscope (SEM) image of the iron-nickel-boron loaded nickel foam composite material obtained in Example 1 is shown;

[0029] Figure 2 The transmission electron microscope (TEM) image of the iron-nickel-boron loaded nickel foam composite material obtained in Example 1 is shown;

[0030] Figure 3 The scanning transmission electron microscope (STEM) image of the iron-nickel-boron-loaded nickel foam composite material obtained in Example 1 is shown ( Figure 3 (a) in the figure), and the corresponding B, Fe and Ni element maps ( Figure 3 (b) to (d));

[0031] Figure 4 A comparison chart of the specific surface area (BET) of the iron-nickel-boron-loaded nickel foam composite material obtained in Example 1 and a catalyst of the same type is shown;

[0032] Figure 5 A schematic diagram of an organic pollutant treatment device constructed by the present invention is shown;

[0033] Figure 6 A comparison chart showing the degradation performance of 2,4-dichlorophenol between the iron-nickel-boron loaded nickel foam composite material obtained in Example 1 and the same type of catalyst is shown;

[0034] Figure 7 The repeatability experimental results of the Fe-Ni-B-loaded nickel foam composite material obtained in Example 1 in the process of degrading 2,4-dichlorophenol are shown;

[0035] Figure 8 The inductively coupled plasma mass spectrometry (ICP-MS) detection result diagram of the iron-nickel-boron loaded nickel foam composite material obtained in Example 1 is shown. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific embodiments, but it should be noted that the present invention is not limited to the following embodiments. The preferred embodiments described here are only for the purpose of illustrating and explaining the present invention.

[0037] Unless otherwise specified, the raw materials used in the embodiments of the present invention are commercially available products and do not require further treatment.

[0038] Example 1

[0039] This embodiment provides a method for preparing a self-supporting Fe-Ni-B-loaded nickel foam composite material, the raw materials used are: nickel foam (NF, 99.5%, 2.0 mm thick, 100 ppi, 480 g·m -2 ), hydrochloric acid (HCl, AR), anhydrous ethanol (C2H6O, ≥99.5%), ferrous chloride tetrahydrate (FeCl2·4H2O, 99%), sodium borohydride (NaBH4, AR), sodium hydroxide (NaOH, ≥97%) and deionized water, follow the steps below:

[0040] S1. Pretreatment of nickel foam substrate:

[0041] The nickel foam substrate was cut into a suitable sample (here 2 cm × 2 cm), immersed in a hydrochloric acid solution with a molar concentration of 1M and ultrasonicated for 15 minutes to remove the oxide layer and impurities on the surface of the nickel foam, and then washed with deionized water until neutral. The nickel foam was repeatedly washed with anhydrous ethanol several times, and then dried at 60°C for 12 hours for use.

[0042] S2. Configuration of reaction solution:

[0043] Ferrous chloride tetrahydrate was dissolved in deionized water to prepare 15 mL of a 20 wt % iron precursor solution; sodium borohydride was dissolved in deionized water to prepare 15 mL of a 10 wt % reducing agent solution, and the pH of the solution was adjusted to 13 using 1 M sodium hydroxide.

[0044] S3, Alternating Immersion Reaction

[0045] A piece of pre-treated nickel foam is immersed in the reducing agent solution, and the time is set for 10 seconds after bubbles are observed. Then, the nickel foam is quickly immersed in the iron precursor solution and reacted for 10 seconds before being taken out.

[0046] S4, step S3 is repeated for several times until the nickel foam is immersed in the reducing agent solution and no bubbles are generated, then the process is stopped. The product is then repeatedly rinsed with deionized water until it is neutral, and then repeatedly washed with anhydrous ethanol for several times, and then dried at 60° C. for 12 hours to obtain a self-supporting iron-nickel-boron loaded nickel foam composite material (Fe-Ni-B@NF).

[0047] For comparison, this example also prepared a nickel-boron-loaded nickel foam composite material without iron, and the method was as follows: immersing the pretreated nickel foam in a reducing agent solution until bubbles no longer appear in the reducing agent solution. The product was then repeatedly rinsed with deionized water until neutral, and then repeatedly washed with anhydrous ethanol for several times, and then dried at 60°C for 12 hours to obtain a self-supporting nickel-boron-loaded nickel foam composite material (Ni-B@NF).

[0048] For comparison, this example also prepared an iron-nickel-loaded nickel foam composite material without boron addition, and the method was as follows: 50 mL of a reaction solution (20 wt% of ferric chloride tetrahydrate, 1 wt% of urea and 0.5 wt% of ammonium fluoride) was prepared, and the solution was transferred to a Teflon-lined stainless steel autoclave with a piece of pretreated nickel foam added, and kept at 120° C. for 8 hours. Thereafter, the solution was washed with deionized water and anhydrous ethanol in sequence, and then dried at 60° C. for 12 hours to obtain an iron-nickel-loaded nickel foam composite material (Fe-Ni@NF).

[0049] Figure 1 and Figure 2The SEM and TEM images of the iron-nickel-boron loaded nickel foam composite material prepared in this embodiment are respectively shown. From the SEM and TEM images, it can be clearly observed that the surface of the iron-nickel-boron loaded nickel foam composite material is evenly distributed with spherical porous nodules and petal-like structures, and the spherical porous nodules and petal-like structures are interconnected in space to form a large number of void spaces. This unique hierarchical porous structure is expected to provide abundant contact areas and multiple transmission channels for reactants, thereby significantly improving catalytic performance. Figure 3 : is an EDS element scanning diagram of the iron-nickel-boron loaded nickel foam composite material prepared in this example. It can be seen from the diagram that iron, nickel and boron elements are uniformly doped in the nickel foam. Figure 4 This is the BET diagram of the iron-nickel-boron-loaded nickel foam composite material prepared in this embodiment. From the figure, it can be seen that the specific surface area of ​​the iron-nickel-boron-loaded nickel foam composite material is 12.097 m 2 / g, much higher than nickel foam (4.657m 2 / g), nickel-boron loaded nickel foam composite (5.417m 2 / g), Fe-Ni loaded nickel foam composite material (4.842m 2 / g), which is consistent with the above conclusion.

[0050] S5. Construction of chlorophenol organic pollutant treatment device:

[0051] like Figure 5 As shown, the chlorophenol organic pollutant treatment device is composed of an oxidant storage tank, an organic pollutant tank, a mixing kettle, and a degradation reaction tank, and a centrifugal pump is used in conjunction with each component. When the organic pollutant treatment device is working, the solution in the organic pollutant tank and the periodate solution in the oxidant storage tank are sent to the mixing kettle by a centrifugal pump, and after being stirred evenly in the mixing kettle, they are sent to the degradation reaction tank by a centrifugal pump. The core component in the degradation reaction tank is a plurality of groups of catalyst modules arranged along the flow direction, which is the place where the oxidation reaction of organic matter occurs. The construction method is: first, a plurality of iron-nickel-boron loaded nickel foam composite materials are fixedly assembled with a stainless steel mold to produce an iron-nickel-boron loaded nickel foam composite material integral catalyst module, and then the catalyst module is arranged in the degradation reaction tank along the flow direction.

[0052] The organic pollutant solution (10 mg / L) containing 2,4-dichlorophenol and the periodate solution (100 mg / L) are respectively loaded into the organic pollutant tank and the oxidant storage tank, and are sent to the mixing kettle by a centrifugal pump at a suitable flow rate ratio (the flow rate ratio in this embodiment is 1:1.2). After being stirred evenly in the mixing kettle, they are transported to the degradation reaction tank by a centrifugal pump. The organic pollutant solution containing periodate flows through the catalyst module, and the iron-nickel-boron loaded nickel foam composite material mineralizes the organic pollutants into CO2 and H2O by activating the periodate decomposition to produce highly active free radicals and electron transfer pathways. The organic pollutants are discharged after the treatment meets the standards. After testing, the final degradation rate of 2,4-dichlorophenol is about 100%.

[0053] Figure 6 This is a comparison chart of the degradation performance of 2,4-dichlorophenol by the iron-nickel-boron loaded nickel foam composite material prepared in this example and the same type of catalyst. It can be seen from the figure that the prepared iron-nickel-boron loaded nickel foam composite material exhibits excellent catalytic activity and can completely degrade organic pollutants within 18 minutes. Figure 7 This is a repeatable experimental diagram of the degradation of 2,4-dichlorophenol by the iron-nickel-boron loaded nickel foam composite material prepared in this embodiment. It can be seen from the figure that the prepared iron-nickel-boron loaded nickel foam composite material still shows excellent degradation effect after being repeated 4 times, indicating that the catalytic effect of the prepared composite material is stable and the active components are firmly distributed.

[0054] Ion leaching experiment (directly measuring the iron and nickel ions in the solution after the reaction), the sample preparation method is: take 5mL of the solution after the degradation reaction and add it to 15mL of 65-68% concentrated nitric acid, and ultrasonicate for 30 minutes. Take 2mL of the supernatant and dilute it to 10mL. The sample is detected by Agilent 7500 Isotope Chronology Laboratory-Laser Ablation Plasma Mass Spectrometer of Agilent Corporation of the United States. Figure 8 This is the ICP-MS test result diagram of the iron-nickel-boron loaded nickel foam composite material obtained in this example. It can be seen from the figure that the iron and nickel ion leaching during the degradation process of the iron-nickel-boron loaded nickel foam composite material is 45.3 and 6.979 PPB, respectively, which are far below the limit values ​​of the World Health Organization and the European Union.

[0055] The above results show that this method solves the defects of the traditional preparation method, such as sediment aggregation, uneven loading, low specific surface area, poor catalytic activity, sediment shedding and large amount of ion leaching during the reaction.

[0056] Example 2

[0057] The preparation method of this embodiment is the same as that of embodiment 1, with the only difference being that in S2, ferrous sulfate heptahydrate is used to prepare the iron precursor solution.

[0058] It is demonstrated that the present embodiment successfully prepared a self-supporting iron-nickel-boron loaded nickel foam composite material.

[0059] Example 3

[0060] The preparation method of this embodiment is the same as that of Embodiment 1, except that: in S5, an organic pollutant solution (10 mg / L) containing 2,4,6-trichlorophenol and a periodate solution (100 mg / L) are respectively loaded into an organic pollutant tank and an oxidant storage tank, and are delivered to a mixing kettle by a centrifugal pump at a suitable flow rate ratio (the flow rate ratio in this embodiment is 1:1.2), stirred evenly in the mixing kettle, and delivered to a degradation reaction tank by a centrifugal pump.

[0061] It was demonstrated that the final degradation rate of 2,4,6-trichlorophenol was approximately 100%.

[0062] Example 4

[0063] The preparation method of this embodiment is the same as that of Embodiment 1, except that in S5, an organic pollutant solution (10 mg / L) containing 4-chlorophenol and a periodate solution (100 mg / L) are respectively loaded into an organic pollutant tank and an oxidant storage tank, and are delivered to a mixing kettle by a centrifugal pump at a suitable flow rate ratio (the flow rate ratio in this embodiment is 1:1.2), stirred evenly in the mixing kettle, and delivered to a degradation reaction tank by a centrifugal pump.

[0064] It was shown that the final degradation rate of 4-chlorophenol was about 100%.

[0065] The above-mentioned embodiments only express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a self-supporting iron-nickel-boron loaded nickel foam composite material, characterized in that: Firstly, the oxide layer and impurities on the surface of nickel foam are removed by pretreatment, and then the nickel foam is alternately immersed in a reducing agent solution and an iron precursor solution by an alternating immersion method, so as to induce the metal ions to self-catalytically grow iron-nickel boride on the surface of nickel foam, thereby obtaining a self-supporting iron-nickel-boron-loaded nickel foam composite material.

2. The method for preparing the self-supporting iron-nickel-boron loaded nickel foam composite material according to claim 1, characterized in that: Proceed as follows: Step 1: Place the nickel foam in a hydrochloric acid solution for treatment, then wash it with deionized water and anhydrous ethanol in sequence, and then place it in a drying oven to dry; Step 2: dissolving an iron salt in deionized water to prepare a 10-20 wt% iron precursor solution; dissolving sodium borohydride in deionized water to prepare a 5-10 wt% reducing agent solution, and adjusting the pH value of the solution to greater than 10 using 0.1-1.0 M sodium hydroxide to prevent self-decomposition of sodium borohydride; Step 3: immerse the nickel foam in a reducing agent solution, and let it stand for 10-20 seconds after bubbles are observed; then quickly immerse it in an iron precursor solution, and take it out after fully reacting for 10-20 seconds; Step 4: Repeat the impregnation process of step 3 until the nickel foam is immersed in the reducing agent solution and no more bubbles are generated. The obtained product is washed and dried to obtain a self-supporting iron-nickel-boron loaded nickel foam composite material.

3. The preparation method according to claim 2, characterized in that: In step 1, the concentration of the hydrochloric acid solution is 1M.

4. The preparation method according to claim 2, characterized in that: In step 2, the iron salt is any one of ferrous chloride tetrahydrate and ferrous sulfate heptahydrate.

5. The preparation method according to claim 1, characterized in that: In step 1 and step 4, the drying condition is drying at 60-80° C. for 8-12 hours.

6. A self-supporting iron-nickel-boron loaded nickel foam composite material prepared by the preparation method according to any one of claims 1 to 5.

7. An application of the self-supporting iron-nickel-boron loaded nickel foam composite material according to claim 6, characterized in that: Activated periodate was used as a catalyst to treat chlorophenol organic pollutants.

8. The use according to claim 7, characterized in that: A chlorophenol organic pollutant treatment device is constructed; the self-supporting iron-nickel-boron loaded nickel foam composite material is assembled into a catalyst module, so that a mixed waste liquid of chlorophenol organic pollutants and periodate flows through the catalyst module, thereby activating the periodate and achieving complete degradation of the chlorophenol organic pollutants.

9. The use according to claim 7 or 8, characterized in that: The periodate includes at least one of potassium periodate and sodium periodate.

10. The use according to claim 7 or 8, characterized in that: The chlorophenol organic pollutant is at least one of 4-chlorophenol, 2,4-dichlorophenol and 2,4,6-trichlorophenol.

Citation Information

Patent Citations

  • Porous nickel-molybdenum electrode material loaded with double-phase boride in situ as well as preparation method and application of porous nickel-molybdenum electrode material

    CN117684201A

  • Anion and cation doped carbon-coated lithium iron phosphate cathode material and preparation method thereof

    CN103887513A

  • Preparation method of self-supporting nanometer flake CoFeB supercapacitor electrode materials

    CN109119257A

  • Cobalt-vanadium-based self-supporting electrode and preparation method and application thereof

    CN114318400A

  • Composite catalyst as well as preparation method and application thereof

    CN115161693A

Cited By

  • Preparation method of boronized MoNi loaded foamed nickel self-supporting catalyst, catalyst and application

    CN122382641A

  • Preparation method of self-supporting catalyst of boronized MoNi loaded foam nickel, catalyst and application

    CN122382641B